2017
DOI: 10.3168/jds.2016-12454
|View full text |Cite
|
Sign up to set email alerts
|

Liver transcriptome analysis reveals important factors involved in the metabolic adaptation of the transition cow

Abstract: During early lactation, dairy cows experience a severe metabolic load often resulting in the development of various diseases. The inevitable deficiency in nutrients and energy at the onset of lactation requires an optimal adaptation of the hepatic metabolism to overcome metabolic stress. We conducted a whole-liver transcriptome analysis for the transition cow to identify novel factors crucial for metabolic adaptation. Liver samples were obtained from 6 Red Holstein dairy cows (parity 2 to 7, mean ± standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…The concomitant low cholesterol concentrations in early lactation likely limit the hepatic triglyceride export despite an upregulation of hepatic cholesterol biosynthesis . Ha et al (2017a) recently showed with a liver transcriptome analysis that pathways associated with cholesterol are essentially involved in adaptation processes of metabolism during the transition period. Forcing NEB with adipose tissue mobilization at a later lactational stage, however, did not result in a considerable lipid accumulation in the liver as cholesterol concentrations were elevated, supporting hepatic triglyceride export (Gross et al, , 2015a.…”
Section: Adaptation Responses Of the Lipid And Ketone Body Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The concomitant low cholesterol concentrations in early lactation likely limit the hepatic triglyceride export despite an upregulation of hepatic cholesterol biosynthesis . Ha et al (2017a) recently showed with a liver transcriptome analysis that pathways associated with cholesterol are essentially involved in adaptation processes of metabolism during the transition period. Forcing NEB with adipose tissue mobilization at a later lactational stage, however, did not result in a considerable lipid accumulation in the liver as cholesterol concentrations were elevated, supporting hepatic triglyceride export (Gross et al, , 2015a.…”
Section: Adaptation Responses Of the Lipid And Ketone Body Metabolismmentioning
confidence: 99%
“…Ha et al (2015Ha et al ( , 2017b showed that phenotypic expressions of the metabolites glucose, nonesterified fatty acids (NEFA), and BHB are associated with a differential expression of genes involved in robustness and resilience traits. The latest technologies such as nextgeneration sequencing and metabolomics allow a more comprehensive view on relevant pathways and potential candidate markers for selection (Loor, 2010;Huber et al, 2016;Ha et al, 2017a). Testing individual cows on farm might be desirable for prediction of metabolic adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with these data is the raised mRNA for FGF21 in dairy cows p.p. (Schlegel et al, 2013;Ha et al, 2017) and of FGF21 concentrations in plasma p.p. and during feed restriction in late-lactating cows (Schoenberg et al, 2011).…”
Section: Gh-igf-1 Axismentioning
confidence: 99%
“…Moreover, the significantly different metabolites were highly correlated with genes within this pathway. Linoleic acid is a doubly unsaturated omega‐6 fatty acid and an essential fatty acid for dairy cows, and it is very important in maintaining bone health, regulating metabolism, and maintaining the reproductive system . There are three main pathway directions of linoleic acid: 1) acetyl‐CoA as the intermedium to produce ketone bodies (ketogenesis, only occurred in the liver), to produce fatty acids (lipogenesis, like cholesterol), or to generate ATP (beta‐oxidation); 2) to convert to arachidonic acid; and 3) to generate THF‐dios through downstream reactions .…”
Section: Discussionmentioning
confidence: 99%